TEOLOGI POLITIK OPOSISI DALAM ISLAM: REKONSTRUKSI NASIHAH, HISBAH, DAN MUHASABAH AL-HUKKAM SEBAGAI BASIS ETIKA CHECKS AND BALANCES DALAM DEMOKRASI KONSTITUSIONAL INDONESIA - Moh. Kurdi; Ach. Maimun; Moh Diyaul Murtadho; Abdullah; Fadlillah; Moh. Chalilurrosyid; Suji (STAI Nusantara Kota Banda Aceh, 2026)
Discourse on Islamic politics has largely centered on the people's obedience to rulers (ulil amri), while the theological foundation for criticism, oversight, and opposition to power has rarely been systematically formulated within the framework of fiqh siyasah. This article examines the concepts of nasihah (sincere counsel), hisbah (public oversight), and muhasabah al-hukkam (evaluation of rulers) as a theological basis for political opposition in Islam, and compares them with checks-and-balances mechanisms in modern constitutional systems. This study employs a descriptive qualitative approach through library research, involving heuristic, verification, interpretation, and synthesis of primary sources (the Qur'an and Hadith) and secondary sources such as journal articles, books, and legislation. The findings show that Islam provides a strong normative basis for oversight and criticism of rulers through the principles of nasihah and hisbah, accompanied by strict ethical limits on open rebellion (khuruj). As a novelty, this article proposes an integrative model of “Islamic Opposition Ethics” that maps these three classical principles onto three pillars of contemporary checks and balances—parliamentary oversight, judicial review, and public oversight through press freedom and civil society—all underpinned by the ethic of tabayyun (fact verification) as a filter against digital political disinformation. This model is expected to enrich contemporary fiqh siyasah discourse and serve as an analytical instrument for strengthening a culture of constructive opposition within Indonesia's constitutional democracy.